Pt/Ni(OH)2–NiOOH/Pd multi-walled hollow nanorod arrays as superior electrocatalysts for formic acid electrooxidation. Issue 12 (10th September 2015) - Xu, Han; Ding, Liang-Xin; Feng, Jin-Xian; Li, Gao-Ren
Abstract : In this work, novel Pt/Ni(OH)2 –NiOOH/Pd multi-walled hollow nanorod arrays are successfully synthesized. Abstract : The catalytic activity and durability are crucial for the development of high-performance electrocatalysts. To design electrocatalysts with excellent electroactivity and durability, the structure and composition are two important guiding principles. In this work, novel Pt/Ni(OH)2 –NiOOH/Pd multi-walled hollow nanorod arrays (MHNRAs) are successfully synthesized. The unique MHNRAs provide fast transport and short diffusion paths for electroactive species and high utilization rate of catalysts. Because of the special surface and synergistic effects, the Pt/Ni(OH)2 –NiOOH/Pd MHNRA electrocatalysts exhibit high catalytic activity, high durability and superior CO poisoning tolerance for the electrooxidation of formic acid in comparison with Pt@Pd MHNRAs, commercial Pt/C, Pd/C and PtRu/C catalysts.